PROTECTIVE EFFECTS OF CILAZAPRIL AGAINST FREE-RADICAL INJURY IN MYOCARDIAL ISCHEMIA-REPERFUSION - YALÇIN, AHMET SUHA; HAKLAR, GONCAGÜL (ACADEMIC PRESS (LONDON) LTD, 1995)
Cilazapril is a prodrug which is rapidly hydrolysed to the pharmacologically active cilazaprilat following absorption to the bloodstream. In clinical pharmacological studies, administration of cilazapril resulted in potent, reversible, selective and competitive angiotensin converting enzyme inhibition. In this study, we have examined the protective effect of cilazapril on a myocardial ischaemia-reperfusion model by using different parameters of lipid peroxidation and protein oxidation. We have observed increased levels of diene conjugates, carbonyls and malondialdehyde as well as protein carbonyls after ischaemia-reperfusion, whereas protein sulphydryl groups were decreased. Our results clearly demonstrate that cilazapril, a non-sulphydryl, long-acting angiotensin converting enzyme inhibitor, has free-radical-scavenging potential in a model comparable to the clinical situation observed in humans.
Keywords: CILAZAPRIL; MYOCARDIAL ISCHEMIA-REPERFUSION; LIPID PEROXIDATION; PROTEIN OXIDATION; ACE-INHIBITORS; CONVERTING ENZYME-INHIBITORS; CONJUGATED DIENES; LIPID PEROXIDE; GLUTATHIONE; TISSUE; HEART; RATS